The relationship between depressive symptoms and job satisfaction in a collectivistic culture: the moderating role of cultural embededdness - Nurul Ain Hidayah Abas,; Kathleen Otto,; Ramayah Thurasamy, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study investigates the moderating role of individual-level cultural orientation and integrating style of conflict management on the relationship between subordinates’ depressive symptoms and job satisfaction in a collectivistic culture. The results from 390 Malaysian respondents revealed that subordinates with lower levels of depressive symptoms display higher job satisfaction, strengthening the Affective Events Theory. Horizontal collectivism, vertical collectivism, and integrating (as a style of conflict management) are hypothesized to buffer the negative consequences of depressive symptoms. Using the Partial Least Squares (PLS-SEM) analysis, results suggested a negative relationship between depressive symptoms and job satisfaction. Supporting our moderating hypothesis, integrating style had an impact on the level of job satisfaction, in which higher job satisfaction was reported for high rather than low use of integrating style. The results provide new insights into the influence of interpersonal relationships in the shaping of a subordinate’s well-being and in relation to the culture in which they are embedded. From a managerial standpoint, intervention and training designed to enhance subordinates’ job satisfaction focusing on interpersonal skills are recommended. This paper describes what is considered to be the first study to examine the relationship between depressive symptoms and job satisfaction in investigating the role of Malaysia as a collectivistic country at the individual level.